IDE-OTALEX C. The big challenge of the first Crossborder SDI between Spain and Portugal - Batista, Teresa (2016)
The SDI implementation is an average difficult work. There should be an understanding between political and scientific interests, technological advances and it is also quite recommended to meet the needs of citizens. A cross-border SDI implementation, where three levels of administration belonging to two countries must be considered, may seem impossible to do, but it is not only a possible task, but also an enriching and useful task to study the reality of the territory and its sustainable development. IDE OTALEXC is the first crossborder spatial data infrastructure characterized for being a distributed, decentralized, modular and collaborative system, based on standards OGC (Open Geospatial Consortium), W3C (World Wide Web Consortium), ISO (International Organization for Standardization) and open source technology.